Brain levels of GABA, glutamate and aspartate in sociable, aggressive and timid mice: an in vivo microdialysis study - Šustková, Magdaléna; Vávrová, Jaroslava; Kršiak, Miloslav (Neuro-endocrinology letters, 2009)
OBJECTIVES: Some individually-housed male mice behave aggressively during encounters with strange males, while others are timid or sociable in the same situation. The objective of the present study was to examine concentrations of glutamate, aspartate, and GABA in the brain of aggressive, timid, and sociable mice. METHODS: Random-bred albino mice were housed individually for three weeks and then classified in three groups (aggressive, timid, and sociable mice) according to their behavior during social interaction with non-aggressive group-housed male mice in a neutral cage. One week after categorization, by means of the social conflict test, levels of glutamate, aspartate, and GABA were measured by in vivo microdialysis of the medial prefrontal cortex (mPFC) of the isolated and group-housed mice. RESULTS: Sociable mice had almost triple the levels of GABA in their mPFC than aggressive or timid mice. No significant differences in aspartate and glutamate levels were found in these three types of individually-housed mice. Forebrain chemistry of group-housed mice did not differ from that of individually-housed mice with the exception of levels of glutamate and GABA which were significantly lower in group-housed mice than in sociable individually-housed mice. CONCLUSION: The present results suggest that GABA might play a role in sociable behavior. Results also corroborate other findings indicating that the GABAergic system represents an important molecular and neuronal substrate for the selective attenuation of anxiety and aggression.
Keywords: Animals; biologické modely; GABA; Aspartic Acid; gamma-Aminobutyric Acid; excitační aminokyseliny; Models, Biological; chování zvířat; Mice; Shyness; Microdialysis; mozek; myši; mikrodialýza; kyselina glutamová; agrese; kyselina asparagová; mikrochemie; Male; Brain; Mice, Inbred ICR; Excitatory Amino Acids; Aggression; Behavior, Animal; myši inbrední ICR; sociální žádoucnost; plachost; Social Behavior; zvířata; mužské pohlaví; sociální chování; Microchemistry; Social Desirability; Glutamic Acid